A study comparing the accuracy of fetal weight estimation using Dare’s Formula and ultrasound in normal weight and obese pregnant women - Maneeratprasert, Phanitra (Hua Hin Medical Journal, 2023)
Background: Prediction of fetal weight is important to improve the efficiency of birth planning and reduce the incidence of birth injury caused by fetal macrosomia. But nowadays, each method of fetal weight estimation is not very accurate, especially in pregnant women who are overweight and obese, which are more common nowadays. Objective: To compare the accuracy of Dair's fetal weight estimation with ultrasound in normal and overweight pregnant women. Materials and Methods: This retrospective study collected data from the medical records of term singleton pregnant women who delivered at Bangbuathong Hospital in Thailand between October 1, 2019, and September 30, 2021. The purpose of the study was to compare the accuracy of fetal weight estimation by ultrasound within five weeks before delivery with the abdominal measurement using Dare’s Formula. They were divided into pregnant women whose BMI before pregnancy was within the normal range (18.5-22.9 kg/m2) and those with BMI over the threshold (> 23kg/m2). The accuracy of fetal weight estimation was determined by the mean of absolute percent error, not more than 10%. Results: There were 215 pregnant women, 103 were normal weight and 112 were overweight. The mean ages were 26.4+6.3 and 28.4+6.3 (p=.02), respectively. The pregnant women in the high BMI group had a higher incidence of pre-existing medical conditions, and pregnancy complications, and delivered infants with higher birth weights than those in the normal BMI group. The overall accuracy of fetal weight estimation using Dare’s Formula and ultrasonography was significantly different (60% vs 79.5%, p<0.0001). In the normal and high BMI groups, ultrasound was more accurate than clinical estimation using Dare’s Formula (83.5% vs 57.3%, p<0.0001), (75.9% vs 62.5%, p<0.03) respectively. Conclusions: Ultrasonography was more accurate in predicting fetal birth weight than Dare’s formula in full-term singleton women.